2014
DOI: 10.1021/jm4019178
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Efficacious Glucocorticoid Receptor Agonists with a Potential for Reduced Clinical Bone Side Effects

Abstract: Synthesis and structure-activity relationship (SAR) of a series of nonsteroidal glucocorticoid receptor (GR) agonists are described. These compounds contain "diazaindole" moieties and display different transcriptional regulatory profiles in vitro and are considered "dissociated" between gene transrepression and transactivation. The lead optimization effort described in this article focused in particular on limiting the transactivation of genes which result in bone side effects and these were assessed in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(67 reference statements)
1
21
0
Order By: Relevance
“…However, Compound 14 demonstrated a dose-dependent increase in the triglycerides and the serum insulin levels that suggested a lack of dissociation based on these biomarkers. A further advance was the realization that, at least apparently, compounds that contain 'diazaindole' moieties and display different transcriptional regulatory profiles in vitro and are considered 'dissociated' between gene transrepression and transactivation seem to be more interesting [50]. These compounds maintained anti-inflammatory activity in vivo in collageninduced arthritis studies in mouse but had reduced effects on bone relevant parameters compared to the widely used synthetic glucocorticoid prednisolone in vivo [50].…”
Section: Other Potential Boehringer Ingelheim Gr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Compound 14 demonstrated a dose-dependent increase in the triglycerides and the serum insulin levels that suggested a lack of dissociation based on these biomarkers. A further advance was the realization that, at least apparently, compounds that contain 'diazaindole' moieties and display different transcriptional regulatory profiles in vitro and are considered 'dissociated' between gene transrepression and transactivation seem to be more interesting [50]. These compounds maintained anti-inflammatory activity in vivo in collageninduced arthritis studies in mouse but had reduced effects on bone relevant parameters compared to the widely used synthetic glucocorticoid prednisolone in vivo [50].…”
Section: Other Potential Boehringer Ingelheim Gr Agonistsmentioning
confidence: 99%
“…A further advance was the realization that, at least apparently, compounds that contain 'diazaindole' moieties and display different transcriptional regulatory profiles in vitro and are considered 'dissociated' between gene transrepression and transactivation seem to be more interesting [50]. These compounds maintained anti-inflammatory activity in vivo in collageninduced arthritis studies in mouse but had reduced effects on bone relevant parameters compared to the widely used synthetic glucocorticoid prednisolone in vivo [50]. Furthermore, a series of non-steroidal 'dissociated' GR agonists was optimized for drug-like properties such as cytochrome P450 inhibition, metabolic stability, aqueous solubility and human ether-a-go-go-related gene (hERG) ion-channel inhibition.…”
Section: Other Potential Boehringer Ingelheim Gr Agonistsmentioning
confidence: 99%
“…PF‐04171327 (fosdagrocorat) is a phosphate ester prodrug of PF‐00251802 (dagrocorat), a selective high‐affinity partial agonist of the glucocorticoid receptor (Figure ). Previous preclinical, phase 1, and phase 2 studies have demonstrated the anti‐inflammatory effects of PF‐04171327 …”
mentioning
confidence: 99%
“…However, the translation of in vitro dissociation markers to preclinical in vivo parameters in mouse models had been previously established with tool compounds from this series and was expected to apply to these ■ EXPERIMENTAL PROCEDURES Synthesis. All compounds (except 9) described herein have been synthesized following the general scheme outlined in previous publications and summarized in Scheme 1: 16,18 A substituted halogenated aminopyridine 5 undergoes a Sonogashira coupling with the alkyne 6, and the coupling product is cyclized under basic conditions to the azaindoles 7. 20 The majority of the synthetic effort was spent on generating the required substituted alkynes and substituted pyridines, where required, compounds were modified further after the key coupling/cyclization sequence.…”
mentioning
confidence: 99%
“…b Maximum efficacy at the highest tested concentration compared to dexamethasone, defined at 100%; maximum concentration tested is 2 μM. optimized compounds 18. (R)-39 was tested in a 9-day type II collagen-induced arthritis model in rats at 3, 10, and 30 mg/kg qd po in 30% cremophor to guide human efficacious concentration projections.…”
mentioning
confidence: 99%